Critical Slip and Characteristics of Induction Motor for Borehole Investigating Devices - Gečys, S.; Smolskas, P. (Elektronika ir Elektrotechnika, 2006)
If the borehole medium temperature did not exceed +2000C, it is successfully used single-phase asynchronous capacitor motor with solid ferromagnetic rotor for the borehole investigating device drive. For the boreholes of which medium temperature exceeds +2000C it is expedient to use two-phase or three-phase induction motor with solid ferromagnetic rotor. There are presented the critical slip and maximum electromagnetic power expressions of the symmetric induction motor with solid ferromagnetic rotor taking into account the inner complex impedance of the power-supply source and the distributed parameters of the long geophysical cable. It has been proved that derived critical slip expression is the general case of a critical slip formula. The algorithm for the study of motor characteristics taking into account the parameters of the equivalent and the supply circuits is presented. Developed program gives possibility to compute the motor characteristics when it is placed in any borehole depth at various environment and borehole medium temperatures. Ill. 4, bibl. 4 (in English; summaries in English, Russian and Lithuanian.).